Dokter Lubis Program - Siti Marlina (Faculty of Medicine, Public Health, and Nursing, 2018)
.....The Indonesian government via a program called Healthy Living Community Movement (GERMAS) emphasizes the principle of healthy life style for community, family and individual to create healthy nation estimated number of children with special needs in Indonesia in 2015 is about 7-10% of the total number of children. In this regards, children with special needs should be assisted to achieve their better condition of health through healthy lifestyle. Handling of children with special needs aims at emphasizing the potential of the children rather than focusing on their barriers, and also maintaining an optimistic attitude to be able to provide medical, psychological, and prevention services. The various conditions of children with special needs are not an excuse to avoid them, but rather generate awareness on respect to the diversity of individuals and give attention and services as ideal as they need. One effort developed to handle children with special needs is the ‘Dokter Lubis’ program (school children as peer educator for children with special needs) which includes promotive, preventive, curative and rehabilitative activities......